DIGITAL LEADERSHIP AND AI INTEGRATION IN HIGHER EDUCATION: TOWARD A HOLISTIC FRAMEWORK FOR SUSTAINABLE QUALITY EDUCATION - Rokimin; Mona Novita; Sofwan Manaf; Fajar Suryono; Miftah Hur Rahman ZH; Zahid Zufar At Thaariq; Dudun Ubaedullah (Program Studi Manajemen Pendidikan Islam, 2026)
Digital transformation has reshaped debates on access, equity, and quality in higher education, with Artificial Intelligence (AI) as a key enabler. This study synthesizes existing literature to examine the intersections between AI integration, digital leadership, pedagogical competency, and equity-oriented practices. Using a Systematic Literature Review (SLR) with the PRISMA framework, the study analyzed 69 peer-reviewed articles (2022–2025) from Scopus and Watase databases. The findings identified three main themes: expanding digital access, advancing learning equity, and improving quality through AI-based pedagogy. Significant regional differences exist; developing countries (such as Indonesia, Vietnam, and Thailand) focus on infrastructure and teacher training, while developed countries emphasize ethics and curriculum innovation. Methodologically, quantitative approaches dominate and theories such as TPACK and TAM are relied upon. The study concludes that AI's impact is maximized when combined with human factors, such as teacher self-efficacy and institutional leadership. AI is not a neutral tool, but rather a transformative force tied to ethics and inclusivity. Future research should prioritize methodological pluralism and long-term evaluation to align technological advances with educational equity